Aramid fiber anti-photoaging oiling agent, anti-ultraviolet aramid fiber and preparation method of aramid fiber anti-photoaging oiling agent and anti-ultraviolet aramid fiber
By applying anti-photoaging oil agent on the surface of para-aramid fibers, using the combination of inorganic nanoparticles and organic ultraviolet stabilizers to form a protective layer to shield and absorb ultraviolet light, solving the problem of aging of aramid fibers under ultraviolet light and extending its service life.
Patent Information
- Application Number
- CN202510237515.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-03
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-03-03
AI Technical Summary
Para-aramid fibers are prone to photoaging and degradation under ultraviolet light, resulting in brittleness, cracking and yellowing, affecting their service life.
An anti-photoaging oil agent is used, which includes a spinning oil agent, an anti-ultraviolet aging agent and a coupling agent. The anti-ultraviolet aging agent is composed of inorganic nanoparticles and an organic ultraviolet stabilizer. By forming a uniform protective layer on the surface of the fiber, the shielding and absorption of ultraviolet light is achieved.
It effectively slows down the ultraviolet aging rate of para-aramid fibers and extends its service life. This method avoids the problem of the ultraviolet absorber being decomposed by strong acids during spinning, and the anti-ultraviolet aging effect is maintained for a long time.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to an aramid fiber anti-light aging oil agent and an anti-ultraviolet aramid fiber and a preparation method thereof, belonging to the technical field of aromatic polyamide fiber spinning aids. Background Art
[0002] Para-aramid fiber has excellent properties such as high strength, high modulus, high temperature resistance, acid resistance, alkali resistance, and light weight, and is widely used in defense, military industry, aerospace, etc. However, para-aramid fiber itself contains chromophores such as amide and benzene ring, so it is very sensitive to ultraviolet rays and easily absorbs a large amount of ultraviolet rays to cause molecular chain breakage, especially when exposed to ultraviolet light in the 280-320 nm band for a long time, it is very easy to photo-age and degrade, resulting in brittleness, cracking and yellowing, which shortens the service life of aramid fabrics and affects the further application of aramid materials.
[0003] At present, there are two main methods for preparing para-aramid fibers with anti-ultraviolet ability: on the one hand, organic or inorganic ultraviolet absorbers are added to the spinning solution, and then the solution is spun into fibers. However, concentrated sulfuric acid must be used as a spinning solvent in the production process of para-aramid, and common ultraviolet absorbers will react with concentrated sulfuric acid, so that the ultraviolet absorption ability cannot be exerted; on the other hand, a layer of finishing agent or coating containing ultraviolet absorbers is directly coated on the fiber surface. For example, the methods disclosed in patent applications with publication numbers CN106592216A and CN112877858A are to coat the surface of aramid fibers with oil containing ultraviolet absorbers, thereby improving the ultraviolet resistance of the fibers. However, the disadvantage of this method is that with the use of the fibers and changes in the environment, the outer finishing agent or coating will be slowly worn away, so that the ultraviolet resistance cannot be retained for a long time.
[0004] Therefore, in order to improve production efficiency and maintain the original fiber properties, improve the UV aging ability of para-aramid fiber, and extend the service life of aramid products, it is necessary to explore a new process with simple process and stable effect. Summary of the invention
[0005] The present invention aims at the deficiencies in the prior art and provides an aramid fiber anti-light aging oil agent and an anti-ultraviolet aramid fiber and a preparation method thereof. After the para-aramid fiber is treated with the anti-light aging oil agent, the fiber surface can have a good blocking and absorbing effect on ultraviolet rays, which can effectively slow down the ultraviolet aging speed of the para-aramid fiber and extend its service life.
[0006] The technical solution of the present invention to solve the above technical problems is as follows: an anti-light aging oil for aramid fiber, the anti-light aging oil comprises a spinning oil, an anti-ultraviolet aging agent and a coupling agent; the anti-ultraviolet aging agent comprises inorganic nanoparticles and an organic ultraviolet stabilizer.
[0007] Furthermore, in parts by weight, the anti-light aging oil agent includes 85.0-90.0 parts of spinning oil agent, 9.0-14.0 parts of anti-ultraviolet aging agent, and 1.0-2.0 parts of coupling agent.
[0008] Furthermore, in terms of weight, the anti-ultraviolet aging agent comprises 3-8 parts of the inorganic nanoparticles and 2-10 parts of the organic high ultraviolet stabilizer.
[0009] Furthermore, the weight ratio of the inorganic nanoparticles to the organic ultraviolet stabilizer is 1:(0.25-2.5).
[0010] Furthermore, the inorganic nanoparticles are nano-SiO2 and nano-TiO2, and the organic ultraviolet stabilizer is a polysiloxane ultraviolet absorber and a hindered amine light stabilizer.
[0011] Furthermore, the coupling agent is a silane coupling agent.
[0012] The invention also discloses a method for preparing an anti-light aging oil for aramid fiber, the preparation method comprising: sequentially adding an anti-ultraviolet aging agent and a coupling agent to a spinning oil, heating the mixture, homogenizing and mixing the mixture using a homogenizer, and filtering the mixture to obtain the anti-light aging oil.
[0013] The present invention also discloses a method for preparing an anti-ultraviolet aramid fiber, the method comprising: applying oil to the para-aramid fiber, and then heating the fiber to achieve thermal cross-linking, so as to obtain the anti-ultraviolet aramid fiber; The oil used in the oiling operation is the aramid fiber anti-light aging oil of the present invention.
[0014] Furthermore, the oiling operation adopts roller oiling method, the oiling temperature is controlled at 55-65° C., and the oiling rate is 1.2-1.4%.
[0015] Furthermore, the heating temperature for achieving thermal crosslinking is 155-165°C.
[0016] The invention also discloses an anti-ultraviolet aramid fiber, and the anti-ultraviolet aramid fiber is prepared according to the preparation method of the invention.
[0017] The beneficial effects of the present invention are: 1. The anti-light aging oil agent of the present invention can form a uniform protective layer on the surface of the aramid fiber, effectively shielding and absorbing ultraviolet light, and the aramid fiber obtained by the preparation method of the present invention has an anti-ultraviolet aging effect that is significantly better than adding an ultraviolet absorber to the spinning solution, and avoids the problem that the ultraviolet absorber is decomposed by a strong acid during the spinning process, affecting the spinning formation, and the like.
[0018] 2. The present invention selects inorganic nanoparticles and organic UV stabilizers with different action forms for use in combination as anti-ultraviolet aging agents, and the effect is significantly better than the use of a single component; the nano-SiO2 and nano-TiO2 particles are different from common UV absorbers, which can not only absorb part of the UV light, but also have a greater function of reflecting or scattering most of the UV light to achieve a protective effect.
[0019] 3. In the preparation method of the anti-ultraviolet aramid fiber described in the present invention, the polysiloxane ultraviolet absorber and the hindered amine light stabilizer undergo high-temperature treatment, and undergo a thermal cross-linking reaction, spreading on the surface of the aramid fiber to form a uniform network structure, which can not only absorb and attenuate ultraviolet light, but also fix nanoparticles on the fiber surface, thereby achieving multiple shielding-absorption effects on ultraviolet light and maintaining the effect for a long time. DETAILED DESCRIPTION
[0020] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.
[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.
[0022] An aramid fiber anti-light aging oil agent comprises a spinning oil agent, an anti-ultraviolet aging agent and a coupling agent; the anti-ultraviolet aging agent comprises inorganic nanoparticles and an organic ultraviolet stabilizer.
[0023] Specifically, in parts by weight, the anti-light aging oil agent includes 85.0-90.0 parts of spinning oil agent, 9.0-14.0 parts of anti-ultraviolet aging agent, and 1.0-2.0 parts of coupling agent.
[0024] Specifically, in terms of weight, the anti-ultraviolet aging agent comprises 3-8 parts of the inorganic nanoparticles and 2-10 parts of the organic ultraviolet stabilizer.
[0025] Preferably, the weight ratio of the inorganic nanoparticles to the organic UV stabilizer is 1:(0.25-2.5).
[0026] Specifically, the inorganic nanoparticles are at least one of nano-SiO2 and nano-TiO2, preferably nano-SiO2; the organic UV stabilizer is at least one of polysiloxane UV absorber and hindered amine light stabilizer, preferably polysiloxane UV absorber. Inorganic nanoparticles have a strong reflective effect on ultraviolet rays, which can achieve the purpose of anti-ultraviolet aging; organic UV stabilizers have a strong absorption effect on ultraviolet light, which can improve the ultraviolet stability of fibers.
[0027] Specifically, the coupling agent is a silane coupling agent, which can improve the surface activity of the surface of the para-aramid fiber and connect the inorganic nanoparticles to the surface of the aramid fiber.
[0028] More specifically, the spinning oil used in the embodiment of the present invention is YTTH-10, the silane coupling agent is KH550, the nano-SiO2 particles are YC-S130X, the nano-TiO2 particles are R-706, the polysiloxane ultraviolet absorber is UV-531, and the hindered amine light stabilizer is LS-119.
[0029] A method for preparing an anti-light aging oil for aramid fiber comprises the following steps: adding an anti-ultraviolet aging agent and a coupling agent to a spinning oil in sequence, heating the mixture, homogenizing and mixing the mixture using a homogenizer, and filtering the mixture to obtain the anti-light aging oil.
[0030] Specifically, the heating temperature is 55-65° C.; the homogenization speed is 3000-4000 r / min; and the homogenization time is 30-40 min.
[0031] The anti-light aging oil is a light yellow oily liquid, the components have good compatibility, and no stratification occurs after being left for 48 hours.
[0032] A method for preparing an anti-ultraviolet aramid fiber, the method comprising: applying oil to a para-aramid fiber, and then heating the fiber to achieve thermal cross-linking, thereby obtaining the anti-ultraviolet aramid fiber; The oil used in the oiling operation is the aramid fiber anti-light aging oil of the present invention.
[0033] Specifically, the oiling operation adopts roller oiling, the oiling temperature is controlled at 55-65°C, the oiling rate is 1.2-1.4%, and the fiber winding speed is controlled at 150-160 m / min. During the oiling process, the anti-ultraviolet aging agent is spread on the fiber surface with the help of the spinning oil agent, and can be evenly attached to the fiber surface, ensuring that the inorganic nanoparticles and the organic ultraviolet stabilizer are evenly dispersed and tightly combined.
[0034] Specifically, the heating temperature for achieving thermal crosslinking is 155-165°C. The organic UV stabilizer forms a multi-dimensional network structure during the subsequent thermal crosslinking process, which not only improves its ability to bind to the fiber, but also further fixes the inorganic nanoparticles on the fiber surface. The two cooperate with each other to jointly attenuate the damage of ultraviolet light to the fiber.
[0035] More specifically, the para-aramid fiber used in the embodiment of the present invention is 1500D para-aramid fiber.
[0036] Disclosed is an anti-ultraviolet aramid fiber, which is prepared according to the preparation method of the present invention.
[0037] Example 1 An aramid fiber anti-light aging oil, comprising the following components by weight: 85.0 parts of spinning oil, 14.0 parts of anti-ultraviolet aging agent (10.0 parts of polysiloxane ultraviolet absorber, 4.0 parts of nano-SiO2 particles), and 1.0 parts of silane coupling agent; Add anti-ultraviolet aging agent and coupling agent to the spinning oil in sequence, control the temperature to 60 °C, stir at 3500 rpm for 30 minutes, fully homogenize and mix evenly, transfer to a cooling kettle for filtration and cooling, and you can get the anti-light aging oil.
[0038] Preparation of a UV-resistant aramid fiber: The oil-free tow is pulled through the winder and sequentially passes through the roller oil tank, high-temperature heat pipe machine, and five-roller traction machine to complete the coating of spinning oil and anti-ultraviolet aging agent on the fiber surface; The traction speed of the five-roller traction machine was set to 150 m / min, the upper oil tank temperature was set to 65 °C, and the heat pipe machine was set to a heat cross-linking temperature of 160 °C. Based on the anti-ultraviolet aging aramid fiber obtained by the above process, two groups of control experiments were designed to verify the anti-ultraviolet aging effect after 72h of ultraviolet aging treatment and the anti-ultraviolet aging effect after 48h of ultraviolet aging treatment after 5 washes. The mechanical property retention rates of the two were 98% and 97% respectively. Example 2 An aramid fiber anti-light aging oil, comprising the following components by weight: 90.0 parts of spinning oil, 9.0 parts of anti-ultraviolet aging agent (6.0 parts of polysiloxane ultraviolet absorber, 3.0 parts of nano-SiO2 particles), and 1.0 parts of silane coupling agent; Add anti-ultraviolet aging agent and coupling agent to the spinning oil in sequence, control the reaction temperature to 60°C, stir at 3500rpm for 30min, mix them evenly after fully homogenizing, transfer them to a cooling kettle for filtration and cooling, and you can get the anti-light aging oil.
[0039] Preparation of a UV-resistant aramid fiber: The oil-free tow is pulled through the winder and sequentially passes through the roller oil tank, high-temperature heat pipe machine, and five-roller traction machine to complete the coating of spinning oil and anti-ultraviolet aging agent on the fiber surface; The traction speed of the five-roller traction machine is set to 150m / min, the upper oil tank temperature is set to 65℃, and the heat pipe machine is set to the heat cross-linking temperature of 160℃; Based on the anti-ultraviolet aging aramid fiber obtained by the above process, two groups of control experiments were designed to verify the anti-ultraviolet aging effect after 72h ultraviolet aging treatment and the anti-ultraviolet aging effect after 48h ultraviolet aging treatment after 5 washes. The comparison found that the mechanical property retention rates of the two were 95% and 94% respectively; Example 3 An aramid fiber anti-light aging oil, comprising the following components by weight: 89.0 parts of spinning oil, 10.0 parts of anti-ultraviolet aging agent (6.0 parts of polysiloxane ultraviolet absorber, 4.0 parts of nano-SiO2 particles), and 1.0 parts of silane coupling agent; Add anti-ultraviolet aging agent and coupling agent to the spinning oil in sequence, control the reaction temperature to 60°C, stir at 3500rpm for 30min, mix them evenly after fully homogenizing, transfer them to a cooling kettle for filtration and cooling, and you can get the anti-light aging oil.
[0040] Preparation of a UV-resistant aramid fiber: The oil-free tow is pulled through the winder and sequentially passes through the roller oil tank, high-temperature heat pipe machine, and five-roller traction machine to complete the coating of spinning oil and anti-ultraviolet aging agent on the fiber surface; The traction speed of the five-roller traction machine is set to 150m / min, the upper oil tank temperature is set to 65℃, and the heat pipe machine is set to the heat cross-linking temperature of 160℃; Based on the anti-ultraviolet aging aramid fiber obtained by the above process, two groups of control experiments were designed to verify the anti-ultraviolet aging effect after 72h of ultraviolet aging treatment and the anti-ultraviolet aging effect after 48h of ultraviolet aging treatment after 5 washes. The mechanical property retention rates of the two were 97% and 95% respectively. Example 4 An aramid fiber anti-light aging oil, comprising the following components by weight: 86.0 parts of spinning oil, 12.0 parts of anti-ultraviolet aging agent (6.0 parts of polysiloxane ultraviolet absorber, 6.0 parts of nano-SiO2 particles), and 2.0 parts of silane coupling agent; Add anti-ultraviolet aging agent and coupling agent to the spinning oil in sequence, control the reaction temperature to 55°C, stir at 4000rpm for 40 min, fully homogenize and mix evenly, transfer to a cooling kettle for filtration and cooling, and the anti-light aging oil can be obtained.
[0041] Preparation of a UV-resistant aramid fiber: The oil-free tow is pulled through the winder and sequentially passes through the roller oil tank, high-temperature heat pipe machine, and five-roller traction machine to complete the coating of spinning oil and anti-ultraviolet aging agent on the fiber surface; The traction speed of the five-roller traction machine was set to 150 m / min, the upper oil tank temperature was set to 60 °C, and the heat pipe machine was set to a heat cross-linking temperature of 165 °C; Based on the anti-ultraviolet aging aramid fiber obtained by the above process, two groups of control experiments were designed to verify the anti-ultraviolet aging effect after 72h of ultraviolet aging treatment and the anti-ultraviolet aging effect after 48h of ultraviolet aging treatment after 5 washes. The mechanical property retention rates of the two were 95% and 94% respectively. Example 5 An aramid fiber anti-light aging oil, comprising the following components by weight: 88.0 parts of spinning oil, 10.0 parts of anti-ultraviolet aging agent (4.0 parts of polysiloxane ultraviolet absorber, 6.0 parts of nano-SiO2 particles), and 2.0 parts of silane coupling agent; Add anti-ultraviolet aging agent and coupling agent to the spinning oil in sequence, control the reaction temperature to 65°C, stir at 3500rpm for 30min, fully homogenize and mix evenly, transfer to a cooling kettle for filtration and cooling, and you can get the anti-light aging oil.
[0042] Preparation of a UV-resistant aramid fiber: The oil-free tow is pulled through the winder and sequentially passes through the roller oil tank, high-temperature heat pipe machine, and five-roller traction machine to complete the coating of spinning oil and anti-ultraviolet aging agent on the fiber surface; The traction speed of the five-roller traction machine is set to 150m / min, the upper oil tank temperature is set to 65℃, and the heat pipe machine is set to the thermal cross-linking temperature of 165℃; Based on the anti-ultraviolet aging aramid fiber obtained by the above process, two groups of control experiments were designed to verify the anti-ultraviolet aging effect after 72h of ultraviolet aging treatment and the anti-ultraviolet aging effect after 48h of ultraviolet aging treatment after 5 washes. The mechanical property retention rates of the two were 98% and 97% respectively. Example 6 An aramid fiber anti-light aging oil, comprising the following components by weight: 89.0 parts of spinning oil, 9.0 parts of anti-ultraviolet aging agent (3.0 parts of polysiloxane ultraviolet absorber, 6.0 parts of nano-SiO2 particles), and 2.0 parts of silane coupling agent; Add anti-ultraviolet aging agent and coupling agent to the spinning oil in sequence, control the reaction temperature to 60°C, stir at 3500rpm for 30 min, fully homogenize and mix evenly, transfer to a cooling kettle for filtration and cooling, and you can get the anti-light aging oil.
[0043] Preparation of a UV-resistant aramid fiber: The oil-free tow is pulled through the winder and sequentially passes through the roller oil tank, high-temperature heat pipe machine, and five-roller traction machine to complete the coating of spinning oil and anti-ultraviolet aging agent on the fiber surface; The traction speed of the five-roller traction machine is set to 150m / min, the upper oil tank temperature is set to 65℃, and the heat pipe machine is set to the thermal cross-linking temperature of 155℃; Based on the anti-ultraviolet aging aramid fiber obtained by the above process, two groups of control experiments were designed to verify the anti-ultraviolet aging effect after 72h of ultraviolet aging treatment and the anti-ultraviolet aging effect after 48h of ultraviolet aging treatment after 5 washes. The mechanical property retention rates of the two were 97% and 95% respectively. Example 7 An aramid fiber anti-light aging oil, comprising the following components by weight: 88.0 parts of spinning oil, 10.0 parts of anti-ultraviolet aging agent (2.0 parts of polysiloxane ultraviolet absorber, 8.0 parts of nano-SiO2 particles), and 2.0 parts of silane coupling agent; Add anti-ultraviolet aging agent and coupling agent to the spinning oil in sequence, control the reaction temperature to 60°C, stir at 3500rpm for 30min, mix them evenly after fully homogenizing, transfer them to a cooling kettle for filtration and cooling, and you can get the anti-light aging oil.
[0044] Preparation of a UV-resistant aramid fiber: The oil-free tow is pulled through the winder and sequentially passes through the roller oil tank, high-temperature heat pipe machine, and five-roller traction machine to complete the coating of spinning oil and anti-ultraviolet aging agent on the fiber surface; The traction speed of the five-roller traction machine was set to 150 m / min, the upper oil tank temperature was set to 65°C, and the heat pipe machine was set to a heat cross-linking temperature of 160°C; Based on the UV-resistant aramid fiber obtained by the above process, two groups of control experiments were designed to verify the anti-UV aging effect after 72 hours of UV aging treatment and the anti-UV aging effect after 48 hours of UV aging treatment after 5 washes. By comparison, it was found that the mechanical property retention rates of the two were 98% and 96%, respectively.
[0045] Example 8 An aramid fiber anti-light aging oil, comprising the following components by weight: 85.0 parts of spinning oil, 14.0 parts of anti-ultraviolet aging agent (10.0 parts of polysiloxane ultraviolet absorber, 4.0 parts of nano-TiO2 particles), and 1.0 parts of silane coupling agent; Add anti-ultraviolet aging agent and coupling agent to the spinning oil in sequence, control the temperature to 60°C, stir at 3500rpm for 30min, fully homogenize and mix evenly, transfer to a cooling kettle for filtration and cooling, and you can get the anti-light aging oil.
[0046] Preparation of a UV-resistant aramid fiber: The oil-free tow is pulled through the winder and sequentially passes through the roller oil tank, high-temperature heat pipe machine, and five-roller traction machine to complete the coating of spinning oil and anti-ultraviolet aging agent on the fiber surface; The traction speed of the five-roller traction machine was set to 150 m / min, the upper oil tank temperature was set to 65°C, and the heat pipe machine was set to a heat cross-linking temperature of 160°C; Based on the anti-ultraviolet aging aramid fiber obtained by the above process, two groups of control experiments were designed to verify the anti-ultraviolet aging effect after 72h of ultraviolet aging treatment and the anti-ultraviolet aging effect after 48h of ultraviolet aging treatment after 5 washes. The mechanical property retention rates of the two were 96% and 98% respectively. Example 9 An aramid fiber anti-light aging oil, comprising the following components by weight: 85.0 parts of spinning oil, 14.0 parts of anti-ultraviolet aging agent (10.0 parts of hindered amine light stabilizer, 4.0 parts of nano-SiO2 particles), and 1.0 parts of silane coupling agent; Add anti-ultraviolet aging agent and coupling agent to the spinning oil in sequence, control the temperature to 60°C, stir at 3500rpm for 30min, fully homogenize and mix evenly, transfer to a cooling kettle for filtration and cooling, and you can get the anti-light aging oil.
[0047] Preparation of a UV-resistant aramid fiber: The oil-free tow is pulled through the winder and sequentially passes through the roller oil tank, high-temperature heat pipe machine, and five-roller traction machine to complete the coating of spinning oil and anti-ultraviolet aging agent on the fiber surface; The traction speed of the five-roller traction machine was set to 150 m / min, the upper oil tank temperature was set to 65°C, and the heat pipe machine was set to a heat cross-linking temperature of 160°C; Based on the anti-ultraviolet aging aramid fiber obtained by the above process, two groups of control experiments were designed to verify the anti-ultraviolet aging effect after 72h of ultraviolet aging treatment and the anti-ultraviolet aging effect after 48h of ultraviolet aging treatment after 5 washes. The mechanical property retention rates of the two were 98% and 96% respectively. Comparative Example 1 This comparative example 1 is substantially the same as the example 1, except that, in the preparation process of the anti-ultraviolet aramid fiber, the thermal crosslinking reaction process at 160° C. is not performed; Based on the UV-resistant aramid fiber obtained by the above process, two groups of control experiments were designed to verify the anti-UV aging effect after 72h UV aging treatment and the anti-UV aging effect after 48h UV aging treatment after 5 washes. By comparison, it was found that the mechanical property retention rates of the two were 87% and 76%, respectively.
[0048] Comparative Example 2 This comparative example 2 is basically the same as Example 1, except that, in the process of preparing the anti-light aging oil, no anti-ultraviolet aging agent and coupling agent are added; Based on the UV-resistant aramid fiber obtained by the above process, two groups of control experiments were designed to verify the anti-UV aging effect after 72h UV aging treatment and the anti-UV aging effect after 48h UV aging treatment after 5 washes. By comparison, it was found that the mechanical property retention rates of the two were 72% and 70%, respectively.
[0049] Comparative Example 3 This comparative example 3 is basically the same as Example 1, except that no coupling agent is added during the preparation of the anti-light aging oil; Based on the UV-resistant aramid fiber obtained by the above process, two groups of control experiments were designed to verify the anti-UV aging effect after 72h UV aging treatment and the anti-UV aging effect after 48h UV aging treatment after 5 washes. By comparison, it was found that the mechanical property retention rates of the two were 93% and 84%, respectively.
[0050] Comparative Example 4 This comparative example 4 is basically the same as Example 1, except that no anti-ultraviolet aging agent is added during the preparation of the anti-light aging oil; Based on the UV-resistant aramid fiber obtained by the above process, two groups of control experiments were designed to verify the anti-UV aging effect after 72h UV aging treatment and the anti-UV aging effect after 48h UV aging treatment after 5 washes. By comparison, it was found that the mechanical property retention rates of the two were 72% and 71%, respectively.
[0051] Comparative Example 5 This comparative example 5 is basically the same as the example 1, except that in the process of preparing the anti-light aging oil, the anti-ultraviolet aging agents used are all polysiloxane ultraviolet absorbers, and do not contain nano-SiO2 particles.
[0052] Based on the UV-resistant aramid fiber obtained by the above process, two groups of control experiments were designed to verify the anti-UV aging effect after 72h UV aging treatment and the anti-UV aging effect after 48h UV aging treatment after 5 washes. By comparison, it was found that the mechanical property retention rates of the two were 80% and 79%, respectively.
[0053] Comparative Example 6 This comparative example 6 is basically the same as the example 1, except that, in the process of preparing the anti-light aging oil, the anti-ultraviolet aging agents used are all nano-SiO2 particles, and no polysiloxane ultraviolet absorber is contained.
[0054] Based on the UV-resistant aramid fiber obtained by the above process, two groups of control experiments were designed to verify the anti-UV aging effect after 72h UV aging treatment and the anti-UV aging effect after 48h UV aging treatment after 5 washes. By comparison, it was found that the mechanical property retention rates of the two were 78% and 78%, respectively.
[0055] Comparative Example 7 This comparative example 6 is basically the same as example 1, except that, in the preparation process of the anti-light aging oil agent, the anti-ultraviolet aging agent used includes 2.0 parts of a polysiloxane ultraviolet absorber and 12.0 parts of nano-SiO2 particles (the weight ratio of the inorganic nanoparticles to the organic polymer ultraviolet absorber is not within the range of 1: (0.25-2.5)).
[0056] Based on the UV-resistant aramid fiber obtained by the above process, two groups of control experiments were designed to verify the anti-UV aging effect after 72h UV aging treatment and the anti-UV aging effect after 48h UV aging treatment after 5 washes. By comparison, it was found that the mechanical property retention rates of the two were 82% and 85%, respectively.
[0057] The performance of the anti-ultraviolet aging aramid fibers obtained in the above embodiments and comparative examples was tested. The specific results are shown in Table 1. The products in each embodiment and comparative example were washed 5 times and then irradiated with ultraviolet light for 48 hours to test the decrease in mechanical indicators. The results are shown in Table 2.
[0058] The performance testing methods involved are: ASTM G154-2023 "Fluorescent Ultraviolet Lamp Irradiation Standard for Non-metallic Materials" and GB / T14344-2022 "Test Method for Tensile Properties of Chemical Fiber Filaments".
[0059] Table 1 Test results of the anti-ultraviolet performance of the anti-ultraviolet aging aramid fibers obtained in the examples and comparative examples
[0060] Table 2 Test results of anti-ultraviolet performance of anti-ultraviolet aging aramid fibers obtained in Examples and Comparative Examples after washing
[0061] As can be seen from Table 1, after 72 hours of ultraviolet irradiation aging test, the anti-ultraviolet aging aramid fibers obtained in Examples 1-9 all maintained a relatively high retention rate of breaking strength and modulus. As can be seen from Table 2, after 5 washes and 48 hours of ultraviolet irradiation, the reduction in breaking strength and modulus of the anti-ultraviolet aging aramid fibers obtained in Examples 1-9 was relatively small. This shows that the anti-ultraviolet aging effect of the anti-light aging oil agent of the present invention on the fiber can still maintain a good effect after multiple washings, and the service life of the aramid products in practical applications will be significantly extended.
[0062] From the comparison of the data of Comparative Example 1 and Example 1, it can be seen that when preparing the anti-ultraviolet aging aramid fiber, if no thermal crosslinking treatment is performed, the fiber will have a significantly decreased breaking strength retention rate and modulus retention rate after ultraviolet irradiation; the breaking strength and modulus also have significant differences before and after washing. The oil agent that has undergone thermal crosslinking reaction has a better anti-ultraviolet aging degree, and the anti-ultraviolet aging agent can be better fixed on the fiber surface after high temperature treatment.
[0063] From the comparison of the data of Comparative Example 2 and Example 1, it can be seen that the addition of the anti-ultraviolet aging agent has a significant improvement in the ultraviolet aging effect of the fiber. Compared with normal products, the breaking strength and modulus of the fiber irradiated with ultraviolet light can be increased by more than 20%.
[0064] From the data comparison between Comparative Example 3 and Example 1, it can be seen that if no coupling agent is added, the anti-ultraviolet aging performance of the fiber will decrease. Adding a coupling agent can make the nano-SiO2 particles better combine with the fiber. The addition of a coupling agent has a promoting effect on improving the anti-ultraviolet aging effect of the fiber.
[0065] From the comparison of the data of Comparative Example 4 and Example 1, it can be seen that only adding a coupling agent without adding an anti-ultraviolet aging agent component does not improve the anti-ultraviolet aging effect of the fiber, and even reduces the breaking strength.
[0066] From the comparison of the data of Comparative Example 5 and Example 1, it can be seen that if the anti-ultraviolet aging agent contains only polysiloxane ultraviolet absorber and does not contain nano-SiO2 particles, the anti-ultraviolet aging performance of the fiber will be reduced.
[0067] From the data comparison of comparative example 6 and embodiment 1, it can be seen that if the anti-ultraviolet aging agent contains only nano-SiO2 particles and does not contain polysiloxane ultraviolet absorber, the anti-ultraviolet aging performance of the fiber is reduced. From the comparison of comparative examples 5, 6 and embodiment 1, it can be seen that the application of polysiloxane ultraviolet absorber and nano-SiO2 particles in the oil agent is more conducive to improving the anti-ultraviolet aging performance of para-aramid fiber. Nano-SiO2 particles have a strong reflection effect on ultraviolet rays, which can achieve the purpose of anti-ultraviolet aging; polysiloxane ultraviolet absorber has a strong absorption effect on ultraviolet light, which can improve the ultraviolet stability of the fiber; in the preparation method of anti-ultraviolet aramid fiber, polysiloxane ultraviolet absorber undergoes high temperature treatment, and a thermal cross-linking reaction occurs by itself, and a uniform network structure is spread on the surface of the aramid fiber, which can not only absorb and attenuate ultraviolet light, but also fix nano-SiO2 particles on the fiber surface, achieving multiple shielding-absorption effects on ultraviolet light, and can achieve long-term effect retention.
[0068] From the comparison of the data of Comparative Example 7 and Example 1, it can be seen that a suitable ratio between the polysiloxane UV absorber and the nano-SiO2 particles is more conducive to obtaining a para-aramid fiber product with excellent UV resistance.
[0069] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0070] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.
Claims
1. An anti-light aging oil for aramid fiber, characterized in that: The anti-light aging oil comprises a spinning oil, an anti-ultraviolet aging agent and a coupling agent; the anti-ultraviolet aging agent comprises inorganic nanoparticles and an organic ultraviolet stabilizer.
2. The aramid fiber anti-light aging oil according to claim 1, characterized in that: In terms of weight, the anti-light aging oil comprises 85.0-90.0 parts of spinning oil, 9.0-14.0 parts of anti-ultraviolet aging agent, and 1.0-2.0 parts of coupling agent.
3. The aramid fiber anti-light aging oil according to claim 2, characterized in that: In terms of weight, the anti-ultraviolet aging agent comprises 3-8 parts of the inorganic nanoparticles and 2-10 parts of the organic ultraviolet stabilizer.
4. The aramid fiber anti-light aging oil according to claim 2, characterized in that: The weight ratio of the inorganic nanoparticles to the organic ultraviolet stabilizer is 1:(0.25-2.5).
5. The anti-light aging oil for aramid fiber according to any one of claims 1 to 3, characterized in that: The inorganic nanoparticles are at least one of nano-SiO2 and nano-TiO2; the organic additives are at least one of polysiloxane ultraviolet absorbers and hindered amine light stabilizers; and the coupling agent is a silane coupling agent.
6. A method for preparing an anti-light aging oil for aramid fiber according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: adding an anti-ultraviolet aging agent and a coupling agent to a spinning oil in sequence, heating the spinning oil, homogenizing and mixing the spinning oil with a homogenizer, and filtering the spinning oil to obtain the anti-light aging oil.
7. A method for preparing UV-resistant aramid fiber, characterized in that: The preparation method comprises: applying oil to the para-aramid fiber, and then heating the fiber to achieve thermal cross-linking, so as to obtain the anti-ultraviolet aramid fiber; The oil used in the oiling operation is the aramid fiber anti-light aging oil according to any one of claims 1 to 5.
8. The method for preparing an ultraviolet resistant aramid fiber according to claim 7, characterized in that: The oiling operation adopts roller oiling method, the oiling temperature is controlled at 55-65°C, and the oiling rate is 1.2-1.4%.
9. The method for preparing an ultraviolet resistant aramid fiber according to claim 7, characterized in that: The heating temperature for achieving thermal crosslinking is 155-165°C.
10. An anti-ultraviolet aramid fiber, characterized in that: The anti-ultraviolet aramid fiber is prepared according to the preparation method according to any one of claims 7-9.
Citation Information
Patent Citations
Anti-ultraviolet aramid fiber material and preparation method thereof
CN112877858A
Polyester fiber based on benzotriazole type ultraviolet ray absorber and preparing method thereof
CN104562660A
Method for preparing high-tenacity low-elongation polyamide 6 fiber
CN106400156A
Preparation method of uvioresistant aramid fiber
CN106592216A
Carbon fiber oiling agent suitable for box-type oxidation furnace
CN116377622A
Cited By
Environment-friendly heat-resistant polypropylene fiber spinning oil and preparation method thereof
CN120485990A
Preparation method of anti-ultraviolet para-aramid fiber and para-aramid fiber
CN122466579A